The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1182/blood-2013-09-527739
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-150 inhibits tumor invasion and metastasis by targeting the chemokine receptor CCR6, in advanced cutaneous T-cell lymphoma

Abstract: Key Points• Aberrantly diminished expression of miR-150 allows advanced CTCL to invade multiple organs with upregulation of CCR6.• MiR-150 inhibits IL-22-CCL20-CCR6 autocrine signaling in advanced CTCL.In this study, we show that microRNA-150 (miR-150) is significantly downregulated in advanced cutaneous T-cell lymphoma (CTCL), and that this downregulation is strongly associated with tumor invasion/metastasis. Inoculation of CTCL cell lines into nonobese diabetic/Shi-scid interleukin 2g (IL-2g) null mice led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 43 publications
1
87
0
Order By: Relevance
“…MicroRNA-150 deregulation has been reported in various cancers, including cutaneous T-cell lymphoma (28) and Burkitt lymphoma (29), as well as in solid cancers, such as in esophagi squamous carcinoma (30), non-small-cell lung carcinoma (31) and colorectal cancer (32). Surprisingly, cellular miR-150 upregulation was not always observed in tumoral tissue when compared with normal tissue; indeed, a lower level of cellular miR-150 is observed in esophagi (30), lung (31) and colorectal cancer (32) and T-cell lymphoma (28). However, when only the tumoral tissue is taken into consideration, low cellular miR-150 expression is always associated with a greater tumoral potential and a poorer prognosis, as confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-150 deregulation has been reported in various cancers, including cutaneous T-cell lymphoma (28) and Burkitt lymphoma (29), as well as in solid cancers, such as in esophagi squamous carcinoma (30), non-small-cell lung carcinoma (31) and colorectal cancer (32). Surprisingly, cellular miR-150 upregulation was not always observed in tumoral tissue when compared with normal tissue; indeed, a lower level of cellular miR-150 is observed in esophagi (30), lung (31) and colorectal cancer (32) and T-cell lymphoma (28). However, when only the tumoral tissue is taken into consideration, low cellular miR-150 expression is always associated with a greater tumoral potential and a poorer prognosis, as confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The expression signature of miR-150 in the plasma indicated that it may serve as a valuable diagnostic and potentially prognostic biomarker for human AML (19). Furthermore, in cutaneous T-cell lymphoma, upregulation of miR-150 inhibited tumor invasion and metastasis by targeting the chemokine CCL20 receptor, CCR6 (20). These results have provided a novel insight into the function of miR-150 as a tumor suppressor in the pathogenesis of hematological malignancies, as well as a basis for novel therapies targeting miR-150 for the treatment of these hematological malignancies discussed above.…”
Section: Role Of Microrna-150 In Solid Tumors (Review)mentioning
confidence: 99%
“…miR-150, frequently downregulated in HCC (Supplementary Fig. S4), acts as a tumor suppressor (29,30). To validate the direct binding between ZFAS1 and miR-150 at endogenous levels, we carried out an RIP with MS2-binding protein (MS2bp), which specifically binds RNA containing MS2-binding sequences (MS2bs).…”
Section: Zfas1 Is Physically Associated With Mir-150mentioning
confidence: 99%